2022
DOI: 10.1111/1749-4877.12671
|View full text |Cite
|
Sign up to set email alerts
|

From trees to fleas: masting indirectly affects flea abundance on a rodent host

Abstract: Mast seeding causes strong fluctuations in populations of forest animals. Thus, this phenomenon can be used as a natural experiment to examine how variation in host abundance affects parasite loads. We investigated fleas infesting yellow‐necked mice in beech forest after 2 mast and 2 non‐mast years. We tested 2 mutually exclusive scenarios: (1) as predicted by classical models of density‐dependent transmission, an increase in host density will cause an increase in ectoparasite abundance (defined as the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…For rodent relative abundance, a weak negative trend was observed regarding ectoparasite presence. Although previous studies have reported a positive relationship between the relative abundances of rodents and ectoparasites (Alkathiry et al., 2022; Baláž et al., 2022), this does not always translate into increased ectoparasite presence, particularly for fleas and ticks (Hawlena et al., 2005; Krasnov et al., 2007).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For rodent relative abundance, a weak negative trend was observed regarding ectoparasite presence. Although previous studies have reported a positive relationship between the relative abundances of rodents and ectoparasites (Alkathiry et al., 2022; Baláž et al., 2022), this does not always translate into increased ectoparasite presence, particularly for fleas and ticks (Hawlena et al., 2005; Krasnov et al., 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Ground‐dwelling rodent species had a higher probability of having ectoparasites. The ectoparasites we obtained from the rodents tended to be ground‐dwelling too, with several of them (e.g., fleas and mites) living in the underground nests of the rodent hosts (Baláž et al., 2022; Dowling, 2006; Krasnov et al., 2021). Similarly, ticks spend their intermediate moulting stages on the ground after they have detached from their hosts (Durden, 2006; Leal et al., 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ectoparasite (mites and ticks) prevalence decreases during the dry season, which might be due to unfavorable environmental conditions (high ambient temperatures and low humidity). Baláž et al (2022) tested how flea burden changes when their rodent hosts increase in response to massive seed production during the so-called "mast years." They found a hump-shaped relationship.…”
Section: Foster Innovation and Facilitate Publications For Zoologymentioning
confidence: 99%
“…Baláž et al. (2022) tested how flea burden changes when their rodent hosts increase in response to massive seed production during the so‐called “mast years.” They found a hump‐shaped relationship. In agreement with basic models of density‐dependent transmission, when host densities were low to intermediate, the abundance of fleas had a positive relationship with rodent abundance.…”
mentioning
confidence: 99%